PENGARUH KEDISIPLINAN, MOTIVASI KERJA DAN KOMPETENSI TERHADAP KINERJA GURU DI BEBERAPA SMK NEGERI KABUPATEN DONGGALA - Ilham, Ilham (Katalogis, 2015)
The purpose of this study is to explore and analyze simultaneous and partial influence of discipline, work motivation, and competency on the performance of teachers. Population in this research consists of 86 certified teachers in 12 public vocational schools in Donggala Regency; 56 teachers from 3 schools selected as sample with census sampling technique. Tool of analysis used is multiplelinear regressions. Simultaneous and partial significantly have influence on teacher’s perfoemance in public vocational schools in Donggala. The results show that the variation in the variables of teacher’s performance in public vocational schools in Donggala Regency can be explained by the variable discipline, work motivation and competency.